EXPECTED SCENARIOS OF RECOVERY FROM THE CRISIS OF ECONOMY OF RUSSIA - V. Makhalin; O. Makhalina (Вестник университета, 2019)
Some expected scenarios of recovery from the crisis of economy of Russia offered by famous economists, scientists, authorities and the governments are considered. Conclusions are formulated.